Opieka prenatalna nad matką dziecka niepełnosprawnego = Prenatal care for the mother of a disabled child - Szefczyk-Polowczyk, Lucyna; Wengel-Woźny, Karina; Respondek, Malwina; Pudło, Hanna (Journal of Education, Health and Sport, 2015)
Szefczyk-Polowczyk Lucyna, Wengel-Woźny Karina, Respondek Malwina, Pudło Hanna. Opieka prenatalna nad matką dziecka niepełnosprawnego = Prenatal care for the mother of a disabled child. Journal of Education, Health and Sport. 2015;5(6):321-332. ISSN 2391-8306. DOI 10.5281/zenodo.18696 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%286%29%3A321-332 https://pbn.nauka.gov.pl/works/567330 http://dx.doi.org/10.5281/zenodo.18696 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 21.04.2015. Revised 28.05.2015. Accepted: 16.06.2015. Opieka prenatalna nad matką dziecka niepełnosprawnego Prenatal care for the mother of a disabled child Lucyna Szefczyk-Polowczyk1, Karina Wengel-Woźny2, Malwina Respondek3, Hanna Pudło3 1 Śląski Uniwersytet Medyczny w Katowicach, Studium Doktoranckie Wydział Farmaceutyczny z Oddziałem Medycyny Laboratoryjnej w Sosnowcu, Polska 2 Śląski Uniwersytet Medyczny w Katowicach, Studium Doktoranckie Wydział Nauk o Zdrowiu w Katowicach, Polska 3 Śląski Uniwersytet Medyczny w Katowicach, Studium Doktoranckie Wydział Zdrowia Publicznego w Bytomiu, Polska 1 Medical University of Silesia, Ph.D. Department of Pharmacy with the Divisionof Laboratory Medicine in Sosnowiec, Poland 2 Medical University of Silesia, Ph.D. Department of Health Sciences in Katowice, Poland 3 Medical University of Silesia, Ph.D. Department of Public Health in Bytom, Poland Słowa kluczowe: badania prenatalne, matka, ciąża, niepełnosprawność. Key words: prenatal tests, mother, pregnancy, disability. Streszczenie Wprowadzenie i cel pracy: Dla większości rodziców wykonanie badań prenatalnych wiąże się z poczuciem bezpieczeństwa psychicznego związanego z prawidłowym przebiegiem ciąży. Diagnostyka prenatalna oferuje szerokie spektrum badań możliwych do przeprowadzenia na różnych etapach zaawansowania ciąży w celu wczesnego rozpoznania wad wrodzonych. Matka z rozpoznaną ciążą ryzyka powinna zostać objęta opieką specjalistyczną w ośrodku o najwyższym stopniu referencyjności, wówczas szanse na przeżycie, a nawet wyleczenie płodu wzrastają. Równie ważne jest zaspokojenie potrzeby informacji dotyczącej aspektów medycznych, ale także praktycznych możliwości uzyskania pomocy (psychologicznej, finansowej, dostępu do rehabilitacji itp.). Celem pracy była ocena istoty badań prenatalnych w diagnostyce niepełnosprawności dziecka oraz ocena dostępności do wsparcia psychologicznego i merytorycznego dla matek po otrzymaniu diagnozy. Materiał i metodyka: Badanie zostało przeprowadzone w pierwszym kwartale 2015 roku wśród matek dzieci niepełnosprawnych. Metodą badawczą w niniejszej pracy był sondaż, techniką badawczą-ankieta. Autorskim anonimowym kwestionariuszem ankiety objęto grupę 60 osób. Wyniki: Większość badanych kobiet przyznała, że ciąża była planowana. Niepokój budzi fakt, iż po otrzymaniu diagnozy znacznej grupie kobiet nie udzielono jakiegokolwiek wsparcia psychologicznego oraz nie poinformowano gdzie po porodzie można szukać pomocy związanej z leczeniem oraz rehabilitacją dziecka. Wnioski: W większości przypadków diagnoza o chorobie dziecka uzyskana podczas badania prenatalnego miała wpływ na dalszy przebieg ciąży. Ankietowane kobiety przyznają, iż nie uzyskały wystarczającego/bądź żadnego wsparcia psychologicznego oraz merytorycznego ze strony personelu medycznego. Abstract Introduction and objectives: For most parents perform prenatal diagnosis is associated with a sense of psychological security associated with normal pregnancy outcome. Prenatal diagnosis offers a wide range of research that can be carried out at various stages of pregnancy to early diagnosis of congenital malformations. Mother diagnosed with the risk of pregnancy should be included in specialist care at the resort with the highest degree of referentiality, then the chances of survival and even cure the fetus grow. Equally important it is to meet the need for information on medical aspects, but also the practical possibility of obtaining assistance. The aim of the study was to assess the substance of prenatal diagnosis of the child’s disability and to assess the availability of psychological and informational support to mothers after receiving the diagnosis. Material and Methods: The study was conducted in the first quarter of 2015 years among mothers of children with disabilities. The research method in this study was a survey research-survey technique. Copyright anonymous questionnaire survey involved a group of 60 people. Results: The majority of women surveyed admitted that the pregnancy was planned. Concern is the fact that after receiving the diagnosis, a large group of women not given any psychological support and were not informed where postpartum, you can seek help related to the treatment and rehabilitation of the child. Conclusions: In most cases, the child’s diagnosis of the disease was achieved in the antenatal have an impact on the further course of pregnancy. Women surveyed admitted that they had not obtained sufficient / or any substantial psychological support and medical staff from the.